2016
DOI: 10.1371/journal.pone.0160274
|View full text |Cite
|
Sign up to set email alerts
|

Is the Karyotype of Neotropical Boid Snakes Really Conserved? Cytotaxonomy, Chromosomal Rearrangements and Karyotype Organization in the Boidae Family

Abstract: Boids are primitive snakes from a basal lineage that is widely distributed in Neotropical region. Many of these species are both morphologically and biogeographically divergent, and the relationship among some species remains uncertain even with evolutionary and phylogenetic studies being proposed for the group. For a better understanding of the evolutionary relationship between these snakes, we cytogenetically analysed 7 species and 3 subspecies of Neotropical snakes from the Boidae family using different chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 42 publications
5
34
2
Order By: Relevance
“…Likewise, a similar pattern has been identified in several species with subtly differentiated XY sex chromosomes, suggesting a differential accumulation of 18S rDNA sequences [Cioffi et al, 2010;Kawagoshi et al, 2014]. However, the degeneration of the sex-specific chromosome is not a necessarily required event, as attested by cases where the sex pair remains morphologically identical [Mank and Ellegren, 2007;Matsubara et al, 2015;Viana et al, 2016], as has also already been observed in several Tetraodontidae species [Kamiya et al, 2012]. In addition, sex chromosomes can evolve independently among vertebrates, even among closely related species [Mank et al, 2006;Matsubara et al, 2006;Henning et al, 2008;Ezaz et al, 2009;Cioffi et al, 2011;Matsubara et al, 2014].…”
Section: Discussionsupporting
confidence: 64%
“…Likewise, a similar pattern has been identified in several species with subtly differentiated XY sex chromosomes, suggesting a differential accumulation of 18S rDNA sequences [Cioffi et al, 2010;Kawagoshi et al, 2014]. However, the degeneration of the sex-specific chromosome is not a necessarily required event, as attested by cases where the sex pair remains morphologically identical [Mank and Ellegren, 2007;Matsubara et al, 2015;Viana et al, 2016], as has also already been observed in several Tetraodontidae species [Kamiya et al, 2012]. In addition, sex chromosomes can evolve independently among vertebrates, even among closely related species [Mank et al, 2006;Matsubara et al, 2006;Henning et al, 2008;Ezaz et al, 2009;Cioffi et al, 2011;Matsubara et al, 2014].…”
Section: Discussionsupporting
confidence: 64%
“…In Boulengerella , they show the expected distribution pattern in the telomeres of all chromosomes. However, an ITS was also observed in the centromeric region of pair 3 in B. lateristriga, B. cuvieri , and B. maculata , which may reflect possible rearrangements that have occurred during their evolutionary history, such as chromosomal fusions or inversions as documented for many other vertebrate species [Meyne et al, 1990;Wiley et al, 1992;Rosa et al, 2012;Viana et al, 2016]. Additionally, ITSs may also be related to a telomerase process to recover chromosome breaks, in which telomeric sequences are added to non-terminal regions of the chromosomes [Flint et al, 1994;Azzalin et al, 2001;Nergadze et al, 2007].…”
Section: Discussionmentioning
confidence: 82%
“…14. An association between intra-chromosomal telomeric DNA and constitutive heterochromatin has been recorded in many vertebrates, and this association is considered a component of the satellite DNA (Meyne et al, 1990;Multani et al, 2001;Rovatsos et al, 2015;Viana et al, 2016). These signals may also represent remnants of ancient chromosomal rearrangements (Metcalfe et al, 2004), indicating potential hotspots of rearrangement (Scouarnec, Gribble, 2012).…”
Section: Discussionmentioning
confidence: 99%